カイヨウ・カイヒョウ カンソク - 河村, 俊行; カワムラ, トシユキ; 滝沢, 隆俊; タキザワ, タカトシ; 大島, 慶一郎; オオシマ, ケイイチロウ; 牛尾, 収輝; ウシオ, シュウキ; Kawamura, Toshiyuki; Takizawa, Takatoshi; Ohshima, Kay. I.; Ushio, Shuki (1997)
P(論文) 1987年から5カ年計画で始まった「南極域における気候変動に関する総合研究計画(ACR)」では, 「海洋-海氷-大気相互作用」の研究が中心課題の一つであった。その目的のために, 1990年から1992年までオングル海峡およびリュツォ・ホルム湾において海洋・海氷観測が勢力的に実施された。海洋観測では定着氷下の海流と海洋構造を解明するために, CTD・電磁流速計・XBTによる観測, 採水観測, および流速計・サーミスタチェインの係留を行った。また航空機による海洋観測も実施した。海氷観測では海氷の構造と成長過程を理解するため, 海氷コアの採取とその解析を行った。この報告では, まず海洋・海氷観測の概要を述べ, 次にオングル海峡を横断する観測点での海氷成長について記し, 最後にオングル海峡に人工的に開けたプールでの海氷の成長について述べる。 A five-year program of Antarctic Climate Research (ACR) started in 1987. Air-ice-sea interaction study was one of the main subjects of the program. Intensive observations for this purpose were conducted in Ongul Strait and Lutzow-Holm Bay in 1990-1992. Measurements by means of CTD, XBT, AXBT and electromagnetic current meter, and seawater sampling was carried out in order to reveal the flow and oceanic structure under fast ice. Current meters and thermistor chains were also moored to collect long-term data. Sea ice cores were sampled and analyzed to determine the structure and growth processes. In this report, we describe first ocean and sea-ice observations in detail, second, structure and development of sea ice at points across Ongul Strait, and last, growth processes of sea ice in an artificial pool in Ongul Strait. departmental bulletin paper